Studi Perencanaan Pembangkit Listrik Hibrid di Kelompok Ternak Sukamaju II - Gani, Ferizandi Qauzar; Mustaqim, Amrina; Maharsi, Retno; Iqbal Damara, Muhammad (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2025)
This study focuses on the generation of energy from biogas and solar power into electricity in Purwodadi Dalam Village. It focuses on assessing both technical and economic feasibility, alongside the environmental benefits of reducing greenhouse gas emissions. The findings indicate that hybrid power plants have the capability to generate 76.365 kWh/year, 132.812 kWh/year, and 17.062 kWh/year, utilizing readily available raw materials. From an economic perspective, the project is projected to achieve net present values of Rp.327.085.000 and Rp.726.808.000, a benefit-cost ratio of 1.99 and 3.21, and investment payback periods of 6 years 9 months and 3 years 15 days. Additionally, the project offers a significant reduction in emissions, with potential reductions of 618,894 tCO2/year, 618,894 tCO2/year, and 18.30 tCO2/year. These results suggest that the development of this renewable energy project is both technically and economically viable